Electricity internet of things based on LPWAN technology - Yongbo CHEN; Yi TANG; Xinwei AI; Bo XU (Dianxin kexue)
Based on the low power consumption wide area network (LPWAN) technology,operation-level cloud-side integration of energy and power of the internet of things program was achieved using the existing power communica-tion network to realize the data back-to-back.It realized the integration of electric power communication network and LPWAN internet of things technology,provided a wide range of mass “small data” connection for the energy of the in-ternet.It had advantages of low-cost,personalized and flexible.It could meet the connection needs of four-in-one,the source network load interaction,temperature monitoring of electrical equipment and power distribution fault indicator.It could also achieve massive small data connection needs of power plants,substations,electric transport infrastructure,distributed generation operation and maintenance,environmental monitoring energy internet business and so on.